Pengaruh Kenaikan Harga BBM Subsidi Terhadap Pengeluaran Konsumsi Rumah Tangga di Kabupaten Tulungagung - Novia Marchelia Putri Az Zahra; Isa Runtu Leluni; Imroatun Nafisah; Ahmad Choiron Nur Rizqi; Novi Khoiriawati (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The government's policy to increase the price of subsidized fuel in September 2022 has affected the economy in Indonesia. Tulungagung Regency as one of the regions in East Java also felt the impact of this policy. The increase in the price of subsidized fuel makes household consumption expenditure also increase. This study aims to fill the gap in the literature and to determine the effect of the increase in the price of subsidized fuel oil (BBM) on household consumption expenditure in Tulungagung Regency. The approach used in this research is a quantitative approach with the type of research used is associative research. The data source used in this research is secondary data derived from the official websites of the Ministry of Energy and Mineral Resources, Pertamina and BPS Tulungagung Regency in the period 2008-2023, as well as other supporting references such as books, research journals, articles, theses, and news. Data collection techniques in this study are literature studies and documentation with data analysis techniques using simple linear regression. The results of this study indicate that there is a significant influence between the increase in subsidized fuel prices on household consumption expenditure in Tulungagung Regency, with a coefficient of determination of 74,7%.